Hybrid Knowledge Communities - Moutevelis, Ioannis (Εθνικό Μετσόβιο πολυτεχνείο.Σχολή Αρχιτεκτόνων Μηχανικών, 2016)
The field of education and in particular on whether the new technologies have or should have influenced the way in which students acquire knowledge today was a stimulus for this diploma project. The aim of it was the creation of an entity, a node in the net, in which we will have the emergence of a virtual place within students will have the opportunity to communicate with each other, have access to knowledge reservoirs and produce new one. All these will be achieved with the help of advanced technologies. This network of entities is placed at architectural schools in the world. Every node of it is characterized by collegiality, rhizomatic relation with the existing buildings, in order to create an upper assemblage and it is placed in the heart of these architectural schools. In addition, it is characterized by hybridity, with adaptable and flexible program depending on the needs of use, it is open and has a networking nature. Architecturally the construction consists of three distinct "layers" which symbolize the physical, digital and space in-between them. The effort of the object going from the physical space to the digital one, achieved through the in-between space, who provide the "bridges". These bridges act as catalysts by which the virtual space of the entity is enabled. The entry in the digital space followed by the feedback of the physical, which will change depending on the action that takes place on the first.